Departamento de Ciências Básicas - Casatti, Cláudio Aparecido; Bedran de Castro, João César; Gonçalves, Alaide; Oliveira, José Américo de; Callera, João Carlos; Dornelles, Rita Cássia Menegati; Ervolino, Edilson; Nakamune, Ana Claudia Stevanato; Garcia, Wilson Galhego; Rizzolo, Roelf Justino Cruz; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Cláudio Aparecido Casatti